Advances in template-based protein docking by utilizing interfaces towards completing structural interactome. (December 2015) - Muratcioglu, Serena; Guven-Maiorov, Emine; Keskin, Özlem; Gursoy, Attila
Highlights: Structural templates are available for majority of the known PPIs. Structural space of protein–protein interfaces keeps growing. Template-based modelling allows genome-wide predictions. Abstract : The increase in the number of structurally determined protein complexes strengthens template-based docking (TBD) methods for modelling protein–protein interactions (PPIs). These methods utilize the known structures of protein complexes as templates to predict the quaternary structure of the target proteins. The templates may be partial or complete structures. Interface based (partial) methods have recently gained interest due in part to the observation that the interface regions are reusable. We describe how available template interfaces can be used to obtain the structural models of protein interactions. Despite the agreement that a majority of the protein complexes can be modelled using the available Protein Data Bank (PDB) structures, a handful of studies argue that we need more template proteins to increase the structural coverage of PPIs. We also discuss the performance of the interface TBD methods at large scale, and the significance of capturing multiple conformations for improving accuracy.